Several Considerations Regarding the Confession Viewed from a Double Trial Perspective Criminal and Civil - NECULCEA, Marius; IONESCU, Bogdan (Journal of Legal Studies, 2014)
Far from exhausting the subject, we have proposed ourselves, in this article, to present a few aspects of the institution of confession from a dual point of view. In the light of the civil procedure, on one hand, the criminal procedure on the other hand respectively. Although the confession, in its core, is and stays the same, it either comes from the statement of a respondent or of a defendant, still, we won’t be able to apply a sole regime, common, not differentiated, for both situations. Between the civil and the criminal, first, fundamentally appears the purpose difference, de ratio legis. Precisely in this purpose differentiation (or of goal, role, sense, finality, if you wish) we believe to be the place of the researches and the souse of answers.